Workload, fatigue, and muscle damage in an under-20 rugby union team over an intensified international tournament - Lacome, M.; Carling, C.; Hager, J.-P.; Dine, G.; Piscione, J. (International Journal of Sports Physiology and Performance, 2018)
Purpose: To examine the effects of an intensified tournament on workload, perceptual and neuromuscular fatigue, and muscle-damage responses in an international under-20 rugby union team. Methods: Players were subdivided into a high-exposure group (HEG, n=13) and a low-exposure group (LEG, n=11) according to match-play exposure time. Measures monitored over the 19-d period included training session (n=10) and match (n=5) workload determined via global positioning systems and session rating of perceived exertion. Well-being scores, countermovement jump height performance, and blood creatine kinase concentrations were collected at various time points. Results: Analysis of workload cumulated across the tournament entirety for training and match play combined showed that high-speed running distance was similar between groups, while a very likely larger session rating of perceived exertion load was reported in HEG vs LEG. In HEG, high-speed activity fluctuated across the 5 successive matches, albeit with no clear trend for a progressive decrease. No clear tendency for a progressive decrease in well-being scores prior to or following matches was observed in either group. In HEG, trivial to possibly small reductions in postmatch countermovement jump performance were observed, while unclear to most likely moderate increases in prematch blood creatine kinase concentrations occurred until prior to match 4. Conclusions: The magnitude of match-to-match changes in external workload, perceptual and neuromuscular fatigue, and muscle damage was generally unclear or small. These results suggest that irrespective of exposure time to match play players generally maintained performance and readiness to play across the intensified tournament. These findings support the need for holistic systematic player-monitoring programs.